Drafting (and Redrafting) Comparative Property Questionnaires - Peter Sparkes (Utrecht Law Review, 2018)
In an edited version of an address to a conference held in Utrecht on ‘Improving Research Methodology’, the author seeks to draw general lessons from his experience over fifteen years in working on comparative projects on the law of immovable property. Lessons are sought in three broad areas, choice of jurisdiction, terminology and overcoming methodological differences.  All comparison is functional, but guidance is provided on what this means in practice in relation to methodological differences in the approach to facts, in securing comparable texts form legal systems of different size and differing greatly in the degree of churn within the system, and how to overcome formulaic responses in the search for a readable narrative.  The author proposes a golden rule of comparison, that a satisfactory questionnaire can only be drafted when its author knows all the answers.